The call for a responsive approach in Danish field archaeology - Nielsen, Simon Kjær; Larsen, Johan Sandvang (Danish Journal of Archaeology, 2024)
This article advocates for the formal adoption of a responsive approach in Danish field archae- ology, utilising a recent case study to exemplify its practical application. In contrast to adhering strictly to predetermined strategies, responsive archaeology underscores the importance of ongoing evaluation and prioritisation during fieldwork to optimise knowledge acquisition and research potential. Despite the informal practice of a responsive approach in many museums within Danish field archaeology, it lacks formal recognition as a legitimate working approach. To accommodate the continual assessment of features, structures, and contexts throughout excavation, guiding methodological choices and preferences, the proposed solution recommends incorporating a prioritisation field into our on-site recordings and then transferring these entries into our archaeological databases and GIS repositories. This would allow archaeologists to self-assess and document the priority assigned to each target during fieldwork, for better post-excavation analysis. This adaptive approach aims to empower excavation teams, enhance transparency, and unlock new potential for future research and excavation strategies.